Weak-lensing calibration of a stellar mass-based mass proxy for redMaPPer and Voronoi Tessellation clusters in SDSS Stripe 82. Issue 1 (1st November 2017) - Pereira, Maria E. S.; Soares-Santos, Marcelle; Makler, Martin; Annis, James; Lin, Huan; Palmese, Antonella; Vitorelli, André Z.; Welch, Brian; Caminha, Gabriel B.; Erben, Thomas; Moraes, Bruno; Shan, Huanyuan
Abstract: We present the first weak lensing calibration of μ⋆, a new galaxy cluster mass proxy corresponding to the total stellar mass of red and blue members, in two cluster samples selected from the SDSS Stripe 82 data: 230 red-sequence Matched-filter Probabilistic Percolation (redMaPPer) clusters at redshift 0.1 ≤ z < 0.33 and 136 Voronoi Tessellation (VT) clusters at 0.1 ≤ z < 0.6. We use the CS82 shear catalogue and stack the clusters in μ⋆ bins to measure a mass-observable power-law relation. For redMaPPer clusters we obtain M 0 = (1.77 ± 0.36) × 10 14 h −1 M⊙, α = 1.74 ± 0.62. For VT clusters, we find M 0 = (4.31 ± 0.89) × 10 14 h −1 M⊙, α = 0.59 ± 0.54 and M 0 = (3.67 ± 0.56) × 10 14 h −1 M⊙, α = 0.68 ± 0.49 for a low and a high redshift bin, respectively. Our results are consistent, internally and with the literature, indicating that our method can be applied to any cluster-finding algorithm. In particular, we recommend that μ⋆ be used as the mass proxy for VT clusters. Catalogues including μ⋆ measurements will enable its use in studies of galaxy evolution in clusters and cluster cosmology.